The effect of openness in a small open monetary union - Seppo Orjasniemi (Bank of Finland, 2010)
In this paper we build a dynamic stochastic general equilibrium model of a small open monetary union with optimal monetary and fiscal policy, to study the transmission of country specific shocks and associated exchange rate fluctuations. We show that movements of the monetary union s exchange rate stabilize the output fluctuations inside the monetary union, reducing the need for fiscal stabilization. We also show that, under the optimal policy, fluctuations in the exchange rate and the union-wide aggregates are affected by the differences in the degree of nominal rigidities among the monetary union member countries.
URN:NBN:fi:bof-20140807246
Keywords: 330